2021
DOI: 10.3390/ijms222212123
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Protein and Peptide Markers in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a non-specific type of kidney disease that causes a gradual decline in kidney function (from months to years). CKD is a significant risk factor for death, cardiovascular disease, and end-stage renal disease. CKDs of different origins may have the same clinical and laboratory manifestations but different progression rates, which requires early diagnosis to determine. This review focuses on protein/peptide biomarkers of the leading causes of CKD: diabetic nephropathy, IgA nephropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 111 publications
(177 reference statements)
2
14
0
Order By: Relevance
“… 29 Through the use of a 2D-DIGE-MALDIQ-TOF strategy and related techniques, Patel et al were able to detect novel DKD-related protein biomarkers in at-risk individuals corresponding to the processes of renal tubulointerstitial fibrosis and tubulointerstitial fibrosis, including apolipoprotein A1, α-1microglobulin, and zinc α-2 glycoprotein. 30 , 31 Guo et al discovered that - 1-antitrypsin - 1-acid glycoprotein, ceruloplasmin, prostate stem cell antigen, APOA4 and other apolipoprotein AIV are prospective protein biomarkers of DKD in 23 diabetic patients and 16 healthy volunteers. 32 Liao et al also observed a significant increase in urinary haptoglobin (Hp) levels in DKD patients, allowing for the more accurate diagnosis and prognostic assessment of individuals with this disease.…”
Section: Urinary Protein Biomarkers Of Dkdmentioning
confidence: 99%
“… 29 Through the use of a 2D-DIGE-MALDIQ-TOF strategy and related techniques, Patel et al were able to detect novel DKD-related protein biomarkers in at-risk individuals corresponding to the processes of renal tubulointerstitial fibrosis and tubulointerstitial fibrosis, including apolipoprotein A1, α-1microglobulin, and zinc α-2 glycoprotein. 30 , 31 Guo et al discovered that - 1-antitrypsin - 1-acid glycoprotein, ceruloplasmin, prostate stem cell antigen, APOA4 and other apolipoprotein AIV are prospective protein biomarkers of DKD in 23 diabetic patients and 16 healthy volunteers. 32 Liao et al also observed a significant increase in urinary haptoglobin (Hp) levels in DKD patients, allowing for the more accurate diagnosis and prognostic assessment of individuals with this disease.…”
Section: Urinary Protein Biomarkers Of Dkdmentioning
confidence: 99%
“…Many hopes to develop innovative diagnostic tools lie in new high-throughput technologies (i.e. ‘omics’) [ 44 ]. Proteomic studies in patients with podocytopathies proposed alpha-1 antitrypsin, transferrin, histatin-3, 39S ribosomal protein L17 and calretinin as new potential urinary markers [ 45 ].…”
Section: Innovations In the Diagnosis Of Podocytopathiesmentioning
confidence: 99%
“…In the past decade, urine proteomic mass spectrometry (MS)-based approaches have provided valuable information about protein contents and urinary peptide in CKD with different etiologies [ 110 ]. So far, several disease-specific biomarkers have been identified, such as CD44 in membranous nephropathy, dipeptidase 1 (DPEP1) and apolipoproteins in focal glomerulosclerosis (FSGS), and the laminin G-like 3 (LG3) fragments of endorepellin in IgA nephropathy [ 110 , 111 ]. Although many studies have been carried out in adults, proteomic analysis of CKD has not widespread transferred into the pediatric realm [ 111 , 112 ].…”
Section: Cardiovascular Risks and Biomarkers In Pediatric Ckdmentioning
confidence: 99%